2014
DOI: 10.18632/oncotarget.2473
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear import of ribosomal proteins is regulated by mTOR

Abstract: Mechanistic target of rapamycin (mTOR) is a central component of the essential signaling pathway that regulates cell growth and proliferation by controlling anabolic processes in cells. mTOR exists in two distinct mTOR complexes known as mTORC1 and mTORC2 that reside mostly in cytoplasm. In our study, the biochemical characterization of mTOR led to discovery of its novel localization on nuclear envelope where it associates with a critical regulator of nuclear import Ran Binding Protein 2 (RanBP2). We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…However, at this stage it is unclear how nutrient-dependent mTOR activity regulates TFEB nuclear export. Multiple studies have shown that mTOR localizes and functions in the nuclear compartment [31][32][33][34][35][36][37] . Therefore, it is possible that a nuclear pool of mTOR is responsible for TFEB phosphorylation and induction of nuclear export.…”
Section: Discussionmentioning
confidence: 99%
“…However, at this stage it is unclear how nutrient-dependent mTOR activity regulates TFEB nuclear export. Multiple studies have shown that mTOR localizes and functions in the nuclear compartment [31][32][33][34][35][36][37] . Therefore, it is possible that a nuclear pool of mTOR is responsible for TFEB phosphorylation and induction of nuclear export.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in yeast, mTOR is not considered to stimulate RP gene expression in mammals, instead exerting its effects on the level of translation (Powers and Walter 1999). Furthermore, nuclear abundance of RPs was recently suggested to be regulated by a subfraction of mTOR found at the nuclear envelope and complex bound to the nuclear import protein Ran Binding protein 2 (RanBP2) (Kazyken et al 2014). The number of identified 5'TOP mRNAs is growing, with recent studies estimating the existence of approximately 150-200 5'TOP mRNAs, exceeding the number of RPs originally suggested to make up this group (Yamashita et al 2008).…”
Section: Mtor In the Regulation Of Protein Synthesis And Ribosome Biomentioning
confidence: 99%
“…Our data indicates that mTOR and nutrient sensing regulate the localization of polÎș, and this pathway more broadly is known to affect nuclear-cytoplasmic shuttling of multiple proteins (84)(85)(86)(87)(88)(89)(90)(91). For example, PI3K/Akt/mTOR signaling has been shown to prevent nuclear accumulation of glycogen synthase kinase 3ÎČ (GSK3ÎČ) such that inhibition of this pathway leads to a robust increase in nuclear GSK3ÎČ (89,90).…”
Section: Discussionmentioning
confidence: 93%